The Stability of Temporary Restorations Fabricated on a Healing Cap for Immediate Loading: An In Vitro Study - Sangho Jun (Applied Sciences, 2018)
The aim of this study was to analyze the load distribution of interim restorations using healing cap during immediate loading implant treatment in vitro. A total of 29 models with interim restorations which were fabricated with healing cap were selected. The pull-out strength was measured with a used healing cap and new healing cap. The compressive strength and sinking distance were also measured. The pull-out strength of interim restoration showed lower value (max. 29.8 N) compared to the natural bite force. The sinking amounts were larger than normal tooth sinking. The sinking amounts of interim restorations fabricated on a healing cap were roughly 3 times (0.3⁻0.5 mm under 450 N) those of normal teeth. The interim restoration on plastic healing cap would be useful for immediate loading implant treatment.